If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = n + 48 Reorder the terms: y = 48 + n Solving y = 48 + n Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 48 + n
| -6(x+3)-16=18+2 | | 20/0.19 | | 205=6x+3(-7x+12) | | 8=96 | | 8x-1=6x+45 | | u-3+2(3u+2)=-3(u+1) | | 5x*x^2= | | 60x(5x)= | | 3(m-5)-6=3(m+3) | | 3*2a= | | y=(x-4)2 | | 7(z-5)-6(2-3z)=12(Z+1) | | (2x-3)(3x+2)=(x-1)(x+1)+(5x+2)(x-14) | | 2=g+21 | | 4.58+0.14=26.42x | | 1/36x144 | | 6-x=26-3x | | (x-5)(x-5)-100=0 | | 7(x+4)-7=2x+5(4+x) | | 2x+14=-21-3 | | -3x+2(-5x-20)=-157 | | .05x-1.4=.06 | | 8+7x=14+x | | 19=a-14 | | 100-x=10+x | | j^2+10j+25=0 | | -6(x+3)-5=-23 | | 2(x-2)-5(x-5)=4(x-8)-2(x-2) | | 5y+70=110 | | -4x-30=27-7x | | n^4-4n^3+3n^2-5n^4+n^3= | | 2r-6+5r=3-6r+7 |